PENGARUH METODE PEMBELAJARAN TUTOR SEBAYA TERHADAP KEMAMPUAN MENULIS TEKS NEGOSIASI SISWA KELAS X SMA NEGERI 8 MEDAN - Lutfi Hari Orlando Ndraha (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This research aims to determine the influence of the Peer Teaching Method on the Negotiation Text Writing Ability of Class X Students of SMA Negeri 8 Medan. The population in this study were all class X students, totaling 280 students. The sample in this study consisted of 70 students in two classes with 35 students each in the control class and 35 students in the experimental class. This research uses an experimental method with a two group posttest research design that uses quantitative research. The research instrument used was an essay test. The results of this study show 1) The ability to write negotiation texts for class 2) The ability to write negotiation texts for class Thus, it resulted that the experimental class score was higher than the control class score. Based on the results of the t test, the value obtained t = 3.75 and then this value was consulted at the significant level α = 0.05 and n = 35, obtained t table = 1.68. Based on these results, it was concluded that tcount>ttable with a value of 3.75>1.68, so that the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. This proves that there is a significant influence on the use of the Peer Teaching Method on the ability to write negotiation texts in class X SMA Negeri 8 Medan.